Application of CNTs-MoS2/SnO2 p-n heterojunction nanocomposites in lithium-sulfur batteries. Issue 1 (18th August 2022) - Yang, Haijiang; Feng, Wangjun; Pu, Zhongsheng; Chen, Jingzhou; Zhao, Wei; Huang, Zhaoyu
Abstract: Compared with traditional secondary batteries such as lithium-ion batteries, lithium-sulfur batteries have a higher theoretical specific capacity (1675 mAh/g) and energy density (2600 Wh/kg), so they are regarded as the most promising one of the lithium batteries. However, it also has problems such as volume expansion during the reaction, poor conductivity of sulfur, serious "shuttle effect" caused by poly-sulfides, and slow electrochemical reaction kinetics. In this paper, a two-step hydrothermal method was used to synthesize CNTs-MoS2 /SnO2 composite materials. We assembled CNTs/MoS2 materials, CNTs/SnO2 materials and CNTs-MoS2 /SnO2 composite materials into batteries and tested their electrochemical performance. The experimental results show that the CNTs-MoS2 /SnO2 composite material has a more significant catalytic effect and a stronger adsorption capacity. The first-lap discharge specific capacity reaches 1369.9 mAh/g at a rate of 0.1 C, and the Coulomb efficiency can reach more than 98%after 150 cycles at 0.2 C. Its excellent performance is due to the synergistic inter-action of p-type semiconductor metal sulfide MoS2 and n-type semiconductor metal oxide SnO2, and the p-n heterojunction interface formed by the two promotes ion and the transmission rate of electrons.